Occupational Traumatism of Members of Vessel`s Crew on Fishing Fleet in the Northern Water`s Basin - Shapovalov K A (Annals of Marine Science - Peertechz Publications, 2017)
The development of the fishing fleet is particularly important because of the need to provide the population with quality seafood. Specificity of work of the floating crew of the fishing fleet is characterized by frequent changes of factors affecting the health status in general. The analysis of traumatism of members of vessel`screw on fishing fleet of the Northern Water`s Basin have been based on 320 occupational traumas on board of vessels with temporary loss of ability to work. On vessels of fishing fleet frequency of traumatism disability was 67.7 per 1,000 workers. It is the lowest in the group of fishermen to 30 years, 1.2 times less than that of the fishermen 30-39 and older age groups, and almost 3 times less than that of crew over 50 years. Among those affected from members of vessel`s crew in all cases were male. The average age of the victims was 32.2 years. Members of vessel`s crew of service of fish products processing receives damage in 3.9 times more frequently the service of operation of the vessel ("deck") and 6.2 times then the service of technical operation of the vessel ("engine-room"). The highest frequency of traumatism was from masters of fi sh processing (275.9). The works of increased danger on fishing vessels are servicing and repair mechanisms of the engine room; with trawl; maintenance of deck machinery; handling by the crew; moving the ladders and decks; with hatch covers. Alcohol intoxication at the time of injury was recorded in 4.1% of the fishermen (2.8). In flight fishermen get damaged 5.0 times more frequently than in port. When sailing in the Arctic fishermen traumatism rate is 3.5 times higher than in temperate latitudes. Fishermen have to work in conditions of icing decks, tools and equipment, low light jobs because of the frequent fogs, they are forced to wear warm clothes that full range of motion, reduces audibility and accuracy of manufacturing operations. The main type of damage to the fishermen there are fractures, traumatic amputation of the fingers mostly and wounds. Severe disease in view of fishermen are traumatic damades of fingers. They are particularly unfavorable in terms of vocational rehabilitation and future employment due to loss of hand function.